Feeding and nourishing a child with cerebral palsy. View from perceptions - García Zapata, Luis Fernando; Restrepo Mesa, Sandra Lucía (Investigación y Educación en Enfermería, 2011)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Objective. To describe perceptions and routines of the informal primary family caregiver towards feeding and nourishing children with cerebral palsy (CP). Methodology. Qualitative study under ethnography focused perspective. Thirteen caregivers of children with CP who lived in Itagui, Antioquia participated. Data collection was performed until its saturation, through semi structured interviews and observation. For data processing and analysis an open, axial and selective coding was performed, category identification, recurrent, atypical and contradictory patterns from which taxonomies were built, were identified. Results. Caregivers perceive that feeding and nourishing children with CP is difficult from birth, and this difficulty stays during the child’s development. Feeding routines are constituted from daily experiences, mother’s feeling towards disability, physical and physiological handicaps of the child. These routines influence the kid’s food intake, nutrition and the acquisition of minimum abilities to eat by himself and it changes the personal, labor, social and family life of the caregiver. Conclusion. Alimentary and nutritional care of children with CP is built by their caregiver from daily experiences. Permanent assistance does not allow basic ability development to self nourish in those kids who can do it, what generates a load in the caregiver.